(untitled) (American Journal of Technology and Applied Sciences, 2024)
Ceruloplasmin is a plasma protein with important functions in copper metabolism and antioxidant defence of the body. Studies show that the concentration of ceruloplasmin can change in response to various physiological and pathological conditions. This article presents the results of a study on the effect of a pronounced inflammatory response on the level of ceruloplasmin and the significance of this protein in clinical practice.